2015
DOI: 10.1371/journal.pone.0139262
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Peripheral Arterial Disease in a Japanese Population

Abstract: Characteristics of peripheral arterial disease (PAD) are the occlusion or stenosis of multiple vessel sites caused mainly by atherosclerosis and chronic lower limb ischemia. To identify PAD susceptible loci, we conducted a genome-wide association study (GWAS) with 785 cases and 3,383 controls in a Japanese population using 431,666 single nucleotide polymorphisms (SNP). After staged analyses including a total of 3,164 cases and 20,134 controls, we identified 3 novel PAD susceptibility loci at IPO5/RAP2A, EDNRA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 48 publications
0
34
1
1
Order By: Relevance
“…This association persisted after adjusting for diabetes mellitus, smoking, lipid levels, prior myocardial infarction, and hypertension, indicating a novel pathophysiological pathway. In another study by Matsukura et al (79), a GWAS with 785 cases and 3383 controls in a Japanese population identified 3 novel PAD susceptibility loci at importin-5 (IPO5)/RAS-related protein 2A, endothelin receptor type A, and histone deacetylase 9. Fine mapping at the IPO5/RAS-related protein 2A locus revealed that an SNP resulting in reduced expression of IPO5 conferred risk of PAD.…”
Section: Studies Of Genetic Determinants Of Human Padmentioning
confidence: 99%
“…This association persisted after adjusting for diabetes mellitus, smoking, lipid levels, prior myocardial infarction, and hypertension, indicating a novel pathophysiological pathway. In another study by Matsukura et al (79), a GWAS with 785 cases and 3383 controls in a Japanese population identified 3 novel PAD susceptibility loci at importin-5 (IPO5)/RAS-related protein 2A, endothelin receptor type A, and histone deacetylase 9. Fine mapping at the IPO5/RAS-related protein 2A locus revealed that an SNP resulting in reduced expression of IPO5 conferred risk of PAD.…”
Section: Studies Of Genetic Determinants Of Human Padmentioning
confidence: 99%
“…Recent genome‐wide association studies have implicated the ET A receptor as a genetic determinant of coronary artery disease,54, 55 carotid atherosclerosis,54 large‐artery stroke,55 and peripheral artery disease,56 suggesting a role of this receptor in atherogenesis across diverse arterial systems. These findings are supported by clinical and preclinical studies that suggest a direct role of the ET A receptor on the development of atherosclerosis 57, 58, 59, 60, 61.…”
Section: Discussionmentioning
confidence: 99%
“…This locus has previously been associated with a variety of vascular phenotypes, including coronary artery disease, carotid plaques, and peripheral arterial disease (in concordant direction with ischaemic stroke), as well as intracranial aneurysm (in concordant direction with intracerebral haemorrhage). [21-24] The locus has also been associated with migraine in candidate gene studies, [25] but this has not been validated in GWA studies. [26] EDNRA encodes the type A receptor ( ET A ) for Endothelin-1 ( ET-1 ), a potent vasoconstrictor with pro-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%